2020
DOI: 10.1051/e3sconf/202016506045
|View full text |Cite
|
Sign up to set email alerts
|

Bidding strategy of power generation companies in the centralized electricity spot market

Abstract: With the development of China’s power market reform, the spot market has gradually opened up. The spot market is characterized by volatility and uncertainty. Generators urgently need to manage spot market trading income and risks to avoid the risk of spot price fluctuations. This paper studies the bidding strategies of power generation companies in the concentrated spot market, proposes a risk-return coordination method based on the probability of winning bids and conducts case verification. The example shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Their joint operation can more effectively satisfy the requirements of the power system [13,14]. Prior studies discussed that the joint operation of nuclear power and pumped storage can satisfy the peak shaving demand of a power grid and ensure the stable operation of nuclear power for the base-load [15,16]. Furthermore, certain studies indicated that the joint operation of nuclear power and pumped storage can reduce the marginal cost of nuclear power over generations and improve the economic advantages of power systems [17].…”
Section: Introductionmentioning
confidence: 99%
“…Their joint operation can more effectively satisfy the requirements of the power system [13,14]. Prior studies discussed that the joint operation of nuclear power and pumped storage can satisfy the peak shaving demand of a power grid and ensure the stable operation of nuclear power for the base-load [15,16]. Furthermore, certain studies indicated that the joint operation of nuclear power and pumped storage can reduce the marginal cost of nuclear power over generations and improve the economic advantages of power systems [17].…”
Section: Introductionmentioning
confidence: 99%